Life satisfaction and psychological wellbeing among medical students: the mediating role of psychological capital - Abo Shereda, Hanaa M.; Alhazmi, Rehab; Kasemy, Zeinab; Dawood, Eman; Jeya Singh, Evangelin Sally; Alkhalaf, Iblouj; Alshehri, Butool; Alanazi, Taghreed (Frontiers in Psychology, 2025)
IntroductionHealth professions students are exposed to a range of academic, social, and emotional challenges, which have been found to affect their psychological well-being negatively.ObjectivesThis study aimed to assess psychological well-being, life satisfaction, and psychological capital levels among health professions students and the mediating role of psychological capital between psychological well-being and life satisfaction.MethodsA descriptive cross-sectional research design was employed using a sample of 217 health professions students from King Saud bin Abdulaziz University for Health Sciences. We utilized the Psychological Capital Questionnaire, Psychological Well-Being Scales, and the Satisfaction with Life Scale to collect data.ResultsFindings revealed that psychological capital score had a positive and statistically significant impact on life satisfaction (Estimate = 0.23, 95% CI: 0.19 to 0.27, p < 0.001) and on psychological well-being (0.86, 95% CI: 0.70 to 1.03, p < 0.001), suggesting that psychological capital acted as a mediating factor in the relationship between psychological well-being and life satisfaction (p < 0.001).ConclusionThis study sheds light on the importance of cultivating psychological capital and its effect on satisfaction of life and psychological well-being in health professions students.